Method for producing sulfide solid electrolyte
By optimizing the composition and processing of sulfide solid electrolytes with controlled glass content and crystallinity, the challenges of maintaining high ionic conductivity and particle adhesion are addressed, resulting in improved battery performance and capacity maintenance.
Patent Information
- Application Number
- JP2022103098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-08-10
- Filing Date
- 2022-06-28
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2038-08-06
AI Technical Summary
Sulfide solid electrolytes with a stable argyrodite crystal structure face challenges in maintaining high ionic conductivity due to the use of glass components, which can make the particles stiff and reduce the contact area, leading to inadequate ionization and potential breakage during battery production.
The development of sulfide solid electrolytes with a specific composition and processing method, including a high glass content, ensures a high area ratio of glass peaks in P-NMR measurement and controlled crystallinity, enhancing adhesion and plastic deformation between particles, thereby improving ionic conductivity and battery performance.
The solution results in sulfide solid electrolytes with improved ionic conductivity and enhanced battery performance, maintaining a high capacity maintenance rate and reducing the risk of particle breakage during battery production.
Smart Images

Figure 0007625556000008 
Figure 0007625556000009 
Figure 0007625556000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a sulfide solid electrolyte. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Among these batteries, lithium-ion batteries have been attracting attention because of their high energy density.
[0003] Currently available lithium-ion batteries use electrolytes containing flammable organic solvents, so they require improvements in structure and materials to prevent short circuits and the installation of safety devices to suppress temperature rises during short circuits.In contrast, lithium-ion batteries, which use solid electrolytes and are made into all-solid-state batteries, do not use flammable organic solvents within the battery, so safety devices can be simplified and they are thought to be superior in terms of manufacturing costs and productivity.
[0004] Sulfide solid electrolytes are known as solid electrolytes used in lithium ion batteries. Various crystal structures of sulfide solid electrolytes are known, but from the viewpoint of expanding the temperature range in which the battery can be used, a stable crystal structure that is unlikely to change over a wide temperature range is suitable. As such a sulfide solid electrolyte, for example, a sulfide solid electrolyte having an Argyrodite type crystal structure (see, for example, Patent Documents 1 to 5) has been developed.
[0005] A sulfide solid electrolyte having a stable phase crystal structure such as an argyrodite crystal structure requires heat treatment at high temperatures (e.g., 550°C) during production. In general, heat treatment at high temperatures promotes crystallization and increases the degree of crystallinity. This can lead to hardening of the sulfide solid electrolyte. If the sulfide solid electrolyte is hard, various problems can occur during battery production. For example, when sulfide solid electrolyte particles are pressed and bonded together to form a solid electrolyte layer (compact molding), the particles are difficult to deform, so the contact area between the particles becomes small, and the formation of ion paths can be insufficient. In addition, when forming an electrode layer, the active material particles used can be broken when mixed with the sulfide solid electrolyte particles. In order to solve the above problems, for example, as described in Patent Document 6, it is conceivable to make the sulfide solid electrolyte contain a large amount of glass. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2010-540396 [Patent Document 2] International Publication WO2015 / 011937 [Patent Document 3] International Publication WO2015 / 012042 [Patent Document 4] JP 2016-24874 A [Patent Document 5] International Publication WO2016 / 104702 [Patent Document 6] JP 2008-103203 A Summary of the Invention [Problem to be solved by the invention]
[0007] Because glass is softer than crystals, adding more glass improves the compaction of sulfide solid electrolytes, but this tends to reduce ionic conductivity, so improving compaction may not contribute to improving the performance of lithium-ion batteries. An object of the present invention is to provide a sulfide solid electrolyte that can provide a lithium ion battery with a high capacity retention rate. [Means for solving the problem]
[0008] According to one embodiment of the present invention, a solid material containing lithium, phosphorus, and sulfur and having a diffraction peak A at 2θ=25.2±0.5 deg and a diffraction peak B at 29.7±0.5 deg in powder X-ray diffraction using CuKα radiation is provided. 31 The ratio of the total area of the glass-derived peaks observed in the P-NMR measurement to the total area of the PS 4 3- The area ratio of the peak derived from glass is 90% or more and 100% or less, and the solid 31 The sulfide solid electrolyte has an area ratio of a peak derived from glass to the total area of all peaks at 60 to 120 ppm observed in P-NMR measurement of 1% to 45%. Effect of the Invention
[0009] According to one embodiment of the present invention, it is possible to provide a sulfide solid electrolyte that can provide a lithium ion battery with a high capacity retention rate. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram for explaining a compaction evaluation using a uniaxial compression device. [Diagram 2] FIG. 1 is a schematic diagram for explaining a compaction evaluation using a uniaxial compression device. [Diagram 3] 1 is an X-ray diffraction pattern of the sulfide solid electrolyte produced in Example 1. [Figure 4] FIG. 4 is an enlarged view of the X-ray diffraction pattern in the vicinity of 2θ=27 to 33 deg, showing a differential curve of the X-ray diffraction pattern. [Diagram 5] FIG. 2 is a solid-state 31P-NMR spectrum of the sulfide solid electrolyte produced in Example 1. [Figure 6] 1 is an X-ray diffraction pattern of the sulfide solid electrolyte produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The sulfide solid electrolyte according to one embodiment of the present invention contains lithium, phosphorus, and sulfur as constituent elements and satisfies the following requirements 1 and 2. Requirement 1 In powder X-ray diffraction using CuKα radiation, it has diffraction peak A at 2θ=25.2±0.5 deg and diffraction peak B at 29.7±0.5 deg. Requirement 2 solid 31 The ratio of the total area of the glass-derived peaks observed in the P-NMR measurement to the total area of the PS 4 3- The area ratio of the peak derived from glass is 90% or more and 100% or less, and the solid 31 The area ratio of the peak derived from the glass to the total area of all peaks in the range of 60 to 120 ppm observed in P-NMR measurement is 1% or more and 45% or less.
[0012] Regarding the above requirement 1, the diffraction peaks A and B are peaks derived from the argyrodite-type crystal structure. In addition to the diffraction peaks A and B, the diffraction peaks of the argyrodite-type crystal structure may also appear at 2θ=15.3±0.5 deg, 17.7±0.5 deg, 31.1±0.5 deg, 44.9±0.5 deg, or 47.7±0.5 deg, for example. The sulfide solid electrolyte of the present embodiment may have these peaks.
[0013] In the present application, the position of the diffraction peak is judged as A±0.5 deg when the median is A, but it is preferable that it is A±0.3 deg. For example, in the case of the above-mentioned diffraction peak at 2θ=25.2±0.5 deg, the median A is 25.2 deg, and it is preferable that it is in the range of 2θ=25.2±0.3 deg. The same applies to the judgment of all other diffraction peak positions in the present application.
[0014] Regarding the above requirement 2, this requirement is satisfied when the sulfide solid electrolyte contains a certain amount of glass and the majority of the glass is PS. 4 3- It means it's glass. The sulfide solid electrolyte contains a certain amount of glass components, which are relatively soft compared to the crystal structure, improving the adhesion between particles when compacted. 4 3- Glass is one of the glass components with a small size, so PS 4 3- It is believed that the large glass content makes plastic deformation easier, which increases the contact area between the particles of the electrode material and the particles of the sulfide solid electrolyte during battery molding, improving battery performance. In addition, the argyrodite crystal structure is PS 4 3- The structure is the basic skeleton, and halogens are uniformly dispersed at specific sites. In this embodiment, for example, a solid electrolyte (precursor) containing an Argyrodite-type crystal structure with high crystallinity is formed by heat treatment, and then a part of the Argyrodite-type crystal structure is vitrified by processing with a media-less grinder. Therefore, it can be assumed that the glass formed by the above processing is in a state similar to the constituent components and distribution (units and halogens) of the Argyrodite-type crystal structure. Therefore, since the glass has very good interface compatibility with the Argyrodite-type crystal structure, it is considered that the decrease in ion conductivity is suppressed compared to the case where a large amount of other glasses is contained.
[0015] In one embodiment of the present invention, PS 4 3- The area ratio of the peak derived from glass is more preferably 95% or more and 100% or less. Furthermore, the area ratio of the peak derived from glass to the total area of all peaks within the range of 60 to 120 ppm is preferably 2% or more and 40% or less, and more preferably 5% or more and 40% or less.
[0016] solid 31 The peak identification and area ratio by P-NMR measurement are 31The signals observed at 60 to 120 ppm in the P-NMR spectrum are separated into individual peaks by the nonlinear least squares method, and calculations are made from the area and half-width of each peak. The argyrodite crystal structure contains PS 4 3- Although it contains the structure, the difference in crystal symmetry and PS 4 3- Due to differences in the coordination of atoms around the structure, each crystal has a solid 31 The chemical shift positions of the peaks obtained by P-NMR measurement are different. 4 3- Structure, P 2 S 7 4- Structure and P 2 S 6 4- Glasses composed of the above structures have been reported, and the chemical shifts of these chemical structures are observed at positions different from the chemical shift positions of the peaks of the above crystals, and the half-widths are significantly different from those of the peaks derived from the crystals. In general, the peaks derived from the crystals have relatively narrow half-widths, and the peaks derived from the glass have relatively wide half-widths. For example, in the measurement results of the examples and comparative examples of the present application, the half-widths of the peaks derived from the crystals are 450 Hz or less, whereas the half-widths of the peaks derived from the glass are wider than 1000 Hz. For the identification of the separated peaks, for example, H. Eckert, Z. Zhang, and H. Kennedy, Chem. Mater. Vol 2, No. 3, 273 (1990) can be referred to. By utilizing the above-mentioned differences, the solid state of the sulfide solid electrolyte can be 31 The P-NMR spectrum can be separated into peaks due to crystals and peaks due to glass, and the area of each can be quantified. Details will be described in the Examples below. Each peak area indicates the amount of phosphorus present in the same surrounding environment.
[0017] In one embodiment of the present invention, the intensity ratio (Ib / Ip) between the peak intensity Ip of the diffraction peak B and the diffraction intensity Ib of the high-angle side skirt of the diffraction peak B is preferably 0.050 or more and 0.200 or less. The peak intensity Ip is the height of a diffraction peak (diffraction peak B) having a peak top within the range of 29.7±0.5 deg 2θ in powder X-ray diffraction measurement using CuKα radiation. When there are two or more diffraction peaks within the above range, the strongest diffraction peak is defined as diffraction peak B.
[0018] The diffraction intensity Ib is the diffraction intensity at the high-angle base of the peak having the peak intensity Ip. Specifically, the diffraction intensity Ib is the diffraction intensity at the minimum angle at which the differential value is 0 and is greater than the peak top angle of the diffraction peak B in the differential curve obtained by smoothing the X-ray diffraction pattern obtained by powder X-ray diffraction measurement and differentiating the periphery of the region including the diffraction peak B. The inventors presume that the diffraction intensity Ib is the intensity of a broad peak (halo pattern) derived from glass (amorphous component), and that a high diffraction intensity Ib indicates that glass is formed in the surface layer of the sulfide solid electrolyte. The formation of a predetermined amount of glass in the surface layer of the sulfide solid electrolyte tends to improve the compactibility of the sulfide solid electrolyte. The intensity ratio (Ib / Ip) is more preferably 0.050 or more and 0.120 or less.
[0019] In the present invention, since the diffraction peak B derived from the crystal structure contained in the sulfide solid electrolyte and the halo pattern derived from the amorphous component overlap, the above-mentioned differential curve is used to separate the two. Details of the powder X-ray diffraction measurement method will be described in the Examples.
[0020] In one embodiment of the present invention, the Si relative half-width of the diffraction peak B is preferably 1.25 or more and 2.50 or less. This requirement specifies that the half-width of the representative diffraction peak (diffraction peak B) of the argyrodite-type crystal structure is narrow. In general, a diffraction peak in a powder X-ray diffraction measurement has a width, and the width of the peak at half the height of the peak height minus the background is called the half-width. It is known that there is a correlation between the half-width and the crystallite size. When the crystallite size is large, the crystallinity is high and the repeating regularity of the crystal structure is high, so that the intensity of the diffraction peak in the powder X-ray diffraction measurement is strong and the half-width is narrow. However, since the half-width of the diffraction peak depends on the measurement device and measurement conditions, it is necessary to compare it with a standard sample as a standard. When the sulfide solid electrolyte is in a glassy state, the half-width becomes extremely large and the diffraction peak becomes broad. Although the sulfide solid electrolyte of the present embodiment contains glass in part, it maintains high crystallinity as a whole, thereby maintaining high ionic conductivity. The Si relative half width of the diffraction peak B is more preferably 1.25 or more and 2.00 or less.
[0021] The Si relative half-width of diffraction peak B is the ratio to the measured value of the Si diffraction peak at 2θ=28.6±0.5 deg, using Si as a standard sample. It is a relative value based on the standard sample in order to correct the variation in the measured value of diffraction peak B due to differences in measuring equipment, etc. The details of the measurement method are shown in the Examples.
[0022] In one embodiment of the present invention, the volume-based average particle diameter (D 50 ) is preferably 0.1 μm or more and 10 μm or less. 50 It is more preferable that the thickness is 0.2 μm or more and 8 μm or less, and further preferably 0.3 μm or more and 6 μm or less.
[0023] The sulfide solid electrolyte according to one embodiment of the present invention may contain a halogen as a constituent element in addition to the above Li, P, and S. Examples of the halogen include F, Cl, Br, and I. In this embodiment, it is preferable that Cl or Br is contained, and it is more preferable that Cl and Br are contained. In addition, it may contain elements such as Si, Ge, Sn, Pb, B, Al, Ga, As, Sb, Bi, etc. In addition, it may contain chalcogen elements (oxygen (O), selenium (Se), tellurium (Te), etc.).
[0024] In the sulfide solid electrolyte according to one embodiment of the present invention, it is preferable that a molar ratio a of lithium to phosphorus (Li / P), a molar ratio b of sulfur to phosphorus (S / P), and a molar ratio c of halogen to phosphorus (X / P) satisfy the following formulas (A) to (C). 5.0≦a≦7.5 (A) 6.5≦a+c≦7.5 (B) 0.5≦a b ≦1.5 (C) (wherein b>0 and c>0 are satisfied.)
[0025] When the sulfide solid electrolyte contains one or more elements M selected from the group consisting of Si, Ge, Sn, Pb, B, Al, Ga, As, Sb, and Bi, the molar ratio of each element in (A) to (C) above is the molar ratio to the total of the element M and phosphorus. For example, the molar ratio a of lithium to phosphorus (Li / P) is Li / (P+M).
[0026] The sulfide solid electrolyte according to one embodiment of the present invention preferably has a composition represented by the following formula (1), for example. Li a (P 1-α M α )S b X c (1) (In the formula, M is one or more elements selected from the group consisting of Si, Ge, Sn, Pb, B, Al, Ga, As, Sb, and Bi, and X is one or more elements selected from the group consisting of F, Cl, Br, and I. a to c satisfy the following formulas (A) to (C). α is 0≦α≦0.3.) 5.0≦a≦7.5 (A) 6.5≦a+c≦7.5 (B) 0.5≦a b ≦1.5 (C) (wherein b>0 and c>0 are satisfied.)
[0027] X in formula (1) is one or more elements selected from the group consisting of F, Cl, Br and I (x 1 , , x n : n is an integer of 1 to 4). X is one type (x 1 ) or 2 types (x 1 , x 2 ) and more preferably two elements. The molar ratio of each element is not particularly limited. It is preferable that α is 0.
[0028] The molar ratios and compositions of the elements described above are not those of the raw materials used in the production, but those of the sulfide solid electrolyte product. The molar ratios of the elements can be controlled, for example, by adjusting the contents of the elements in the raw materials.
[0029] In this application, the molar ratio and composition of each element in the sulfide solid electrolyte are measured by ICP optical emission spectrometry, except in special circumstances such as when the analysis is difficult. The measurement method of ICP optical emission spectrometry is described in the Examples.
[0030] The sulfide solid electrolyte of the present embodiment can be produced, for example, by treating a sulfide solid electrolyte having an argyrodite-type crystal structure (hereinafter, the sulfide solid electrolyte having an argyrodite-type crystal structure before being treated with a media-less grinder is referred to as a precursor) with a media-less grinder. The method for producing the precursor is not particularly limited. For example, the above-mentioned Patent Documents 1 to 5 can be referred to. In one embodiment of the present invention, the precursor is preferably produced through a heat treatment. By the heat treatment, a precursor containing an argyrodite-type crystal structure with high crystallinity can be obtained. After the argyrodite-type crystal structure is once generated, it is processed with a media-less grinder to vitrify a part of it, thereby obtaining PS 4 3- The proportion of glass can be made extremely high. Hereinafter, one embodiment of the manufacturing method of the present invention will be described.
[0031] In this embodiment, the precursor is obtained by applying mechanical stress to raw materials containing lithium, phosphorus, and sulfur to mix or react them to form a raw material mixture and / or a glassy intermediate, and then heat-treating the intermediate. The raw materials used are a combination of two or more compounds or simple substances that, as a whole, contain the elements essential to the sulfide solid electrolyte to be produced, that is, lithium, phosphorus, and sulfur.
[0032] Examples of raw materials containing lithium include lithium sulfide (Li 2 S), lithium oxide (Li 2 O), lithium carbonate (Li 2 CO 3 and lithium metal alone. Among these, lithium sulfide is preferred. The lithium sulfide can be used without any particular limitation, but is preferably high purity lithium sulfide. Lithium sulfide can be produced by the methods described in, for example, JP-A-7-330312, JP-A-9-283156, JP-A-2010-163356, and JP-A-2011-84438. Specifically, lithium hydroxide and hydrogen sulfide are reacted in a hydrocarbon organic solvent at 70° C. to 300° C. to generate lithium hydrosulfide, and then this reaction liquid is dehydrosulfided to synthesize lithium sulfide (JP 2010-163356 A). Alternatively, lithium hydroxide and hydrogen sulfide can be reacted in an aqueous solvent at 10° C. to 100° C. to produce lithium hydrosulfide, and then this reaction liquid can be dehydrosulfided to synthesize lithium sulfide (JP 2011-84438 A).
[0033] Examples of phosphorus-containing raw materials include diphosphorus trisulfide (P 2 S 3 ), diphosphorus pentasulfide (P 2 S 5 ) and other phosphorus sulfides, sodium phosphate (Na 3 PO 4 ) and other phosphorus compounds, and phosphorus element. Among these, phosphorus sulfide is preferred, and diphosphorus pentasulfide is more preferred. Phosphorus compounds such as diphosphorus pentasulfide and other phosphorus elements can be used without any particular limitation as long as they are industrially produced and commercially available.
[0034] When the sulfide solid electrolyte contains a halogen, the raw material preferably contains, for example, a halogen compound represented by the following formula (2). M l -X m (2)
[0035] In formula (2), M represents sodium (Na), lithium (Li), boron (B), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), germanium (Ge), arsenic (As), selenium (Se), tin (Sn), antimony (Sb), tellurium (Te), lead (Pb), bismuth (Bi), or any of these elements bonded to an oxygen element or a sulfur element, with Li or P being preferred, and Li being more preferred. X is a halogen selected from F, Cl, Br and I. In addition, l is an integer of 1 or 2, and m is an integer of 1 to 10. When m is an integer of 2 to 10, that is, when there are multiple Xs, Xs may be the same or different. For example, SiBrCl 3 In the formula, m is 4 and X is composed of two different elements, Br and Cl.
[0036] Specific examples of the halogen compound represented by the above formula (2) include sodium halides such as NaI, NaF, NaCl, and NaBr; lithium halides such as LiF, LiCl, LiBr, and LiI; 3 , BBr 3 , B.I. 3 Boron halides such as AlF 3 , AlBr 3 ,AlI 3 , AlCl 3 Aluminum halides such as SiF 4 , SiCl 4 , SiCl 3 , Si 2 Cl 6 , SiBr 4 , SiBrCl 3 , SiBr 2 Cl 2 , SiI 4 Silicon halides such as PF 3 , P.F. 5 , PCl 3 , PCl 5 , POCl 3 , PSCl 3 , PBr 3 , PSBr 3 , PBr 5 , POBr 3 , P.I. 3 , P.S.I. 3 , P 2 Cl 4 , P 2 I 4 Phosphorus halides such as SF 2 ,SCIENCE FICTION 4 ,SCIENCE FICTION 6 , S 2 F 10 , SCl 2 , S 2 Cl 2 , S 2 Br 2 Sulfur halides such as GeF 4 , GeCl 4 , GeBr 4 , GeI 4 , GeF 2 , GeCl 2 , GeBr 2 , GeI 2Germanium halides such as AsF 3 , AsCl 3 , AsBr 3 , AsI 3 , AsF 5 Arsenic halides such as SeF 4 , S.E.F. 6 , SeCl 2 , SeCl 4 , Se 2 Br 2 , SeBr 4 Selenium halides such as SnF 4 , SnCl 4 , SnBr 4 , SnI 4 , SnF 2 , SnCl 2 , SnBr 2 , SnI 2 Tin halides such as SbF 3 , SbCl 3 , SbBr 3 , SbI 3 , SbF 5 , SbCl 5 Antimony halides such as TeF 4 , Te 2 F 10 , TeF 6 , TeCl 2 , TeCl 4 , TeBr 2 , TeBr 4 , TeI 4 Tellurium halides such as PbF 4 , PbCl 4 , PbF 2 , PbCl 2 , PbBr 2 , PbI 2 Lead halides such as BiF 3 , BiCl 3 , BiBr 3 , BiI 3 and the like.
[0037] Among them, lithium halides such as lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), phosphorus pentachloride (PCl 5 ), phosphorus trichloride (PCl3 ), phosphorus pentabromide (PBr 5 ), phosphorus tribromide (PBr 3 Among them, lithium halides such as LiCl, LiBr, and LiI, PBr 3 is preferred, and lithium halides such as LiCl, LiBr, and LiI are more preferred, with LiCl and LiBr being even more preferred. The halogen compound may be used alone or in combination of two or more of the above compounds.
[0038] In this embodiment, the composition contains a lithium compound, a phosphorus compound, and a halogen compound, and it is preferable that at least one of the lithium compound and the phosphorus compound contains sulfur. A combination of lithium sulfide, phosphorus sulfide, and a lithium halide is more preferable, and a combination of lithium sulfide, diphosphorus pentasulfide, and a lithium halide is even more preferable.
[0039] For example, when lithium sulfide, diphosphorus pentasulfide, and lithium halide are used as precursor raw materials, the molar ratio of the input raw materials can be lithium sulfide:diphosphorus pentasulfide:lithium halide=37-88:8-25:0.1-50.
[0040] In this embodiment, the raw material is subjected to a mechanical stress to react and produce an intermediate. Here, "applying mechanical stress" means mechanically applying a shearing force, an impact force, or the like. Examples of means for applying mechanical stress include a grinder such as a planetary ball mill, a vibration mill, or a rolling mill, and a kneader. In this embodiment, it is preferable to apply mechanical stress to the raw materials to cause a reaction and turn them into glass. That is, the raw material powder is pulverized and mixed to a state where it cannot maintain its crystallinity by applying a mechanical stress stronger than that of the conventional method. It is presumed that this allows the sulfide solid electrolyte of this embodiment to exhibit high ionic conductivity.
[0041] As for the conditions of the grinding and mixing, for example, when a planetary ball mill is used as a grinder, the rotation speed may be several tens to several hundreds of revolutions per minute, and the processing time may be 0.5 to 100 hours. More specifically, in the case of the planetary ball mill (manufactured by Fritsch: model number P-7) used in the examples of the present application, the rotation speed of the planetary ball mill is preferably 350 rpm or more and 400 rpm or less, and more preferably 360 rpm or more and 380 rpm or less. When balls serving as grinding media are used, for example, zirconia balls, their diameter is preferably 0.2 to 20 mm.
[0042] The intermediate produced by pulverization and mixing is heat-treated to produce a precursor. The heat treatment temperature is preferably 350 to 480°C, more preferably 360 to 460°C, and even more preferably 380 to 450°C. The atmosphere for the heat treatment is not particularly limited, but is preferably an inert gas atmosphere such as nitrogen or argon, rather than a hydrogen sulfide stream.
[0043] The sulfide solid electrolyte of this embodiment can be produced by treating the precursor with a media-less grinder. A media-less grinder is a grinder, a stirrer, or the like that does not use grinding media (media). The sulfide solid electrolyte of this embodiment contains glass in part and has a large amount of argyrodite-type crystal structure. In addition, the ratio of PS to the total glass is 4 3- The glass ratio is high. Therefore, the force applied to the precursor during processing with a media-less grinder must be adjusted so as not to destroy the argyrodite crystal structure excessively. If the argyrodite crystal structure is destroyed, the precursor becomes glassy, and the PS 4 3- Glass components other than glass, e.g. P 2 S 7 4- Glass and P 2 S 6 4- The proportion of glass tends to be high.
[0044] For example, in a grinding method using zirconia balls, depending on the grinding conditions, the force applied to the precursor is too strong, and the argyrodite crystal structure of the precursor tends to be excessively destroyed. When a media-less grinder is used, the force caused by the collision between the precursors is mainly used for processing, which is weaker than when grinding media is used. The processing of this embodiment is preferably carried out with a force similar to that when a media-less grinder is used.
[0045] The media-less pulverizer is preferably a device selected from the group consisting of an airflow pulverizer, a thin film rotary mixer, a high-speed rotary impact mill, and a thermal plasma processor. For example, a jet mill can be used as the airflow pulverizer. For example, Filmix (registered trademark) can be used as the thin film rotary mixer. The treatment may be a dry type or a wet type. For example, the dry type is preferable from the viewpoint of being able to eliminate the drying step. The precursor may be pulverized by the treatment.
[0046] In one embodiment of the present invention, it is preferable not to perform a heat treatment on the sulfide solid electrolyte obtained by the above media-less pulverizer. This is because there is a risk that the glass obtained by the treatment with the media-less pulverizer will recrystallize due to the heat treatment. Note that the heat treatment after the treatment with the media-less pulverizer means, for example, a heat treatment at a temperature of 300°C or higher. If the temperature is such that the glass does not crystallize, the heat treatment may be performed after the treatment with the media-less pulverizer.
[0047] The sulfide solid electrolyte of the present invention can be used for a solid electrolyte layer, a positive electrode, a negative electrode, etc. of a lithium ion secondary battery or the like.
[0048] [Electrode composite material] An electrode mixture according to one embodiment of the present invention includes the above-mentioned sulfide solid electrolyte of the present invention and an active material. Alternatively, the electrode mixture is produced from the sulfide solid electrolyte of the present invention. When a negative electrode active material is used as the active material, the electrode mixture becomes a negative electrode mixture. On the other hand, when a positive electrode active material is used, the electrode mixture becomes a positive electrode mixture.
[0049] ·Negative electrode composite material A negative electrode mixture is obtained by blending a negative electrode active material with the sulfide solid electrolyte of the present invention. As the negative electrode active material, for example, a carbon material, a metal material, etc. can be used. A composite of two or more of these materials can also be used. In addition, negative electrode active materials that will be developed in the future can also be used. In addition, the negative electrode active material preferably has electronic conductivity. Examples of carbon materials include graphite (e.g., artificial graphite), graphite carbon fiber, resin-calcined carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon. Examples of the metal material include simple metals, alloys, and metal compounds. Examples of the simple metals include metal silicon, metal tin, metal lithium, metal indium, and metal aluminum. Examples of the alloys include alloys containing at least one of silicon, tin, lithium, indium, and aluminum. Examples of the metal compounds include metal oxides. Examples of the metal oxides include silicon oxide, tin oxide, and aluminum oxide.
[0050] The mixing ratio of the negative electrode active material and the solid electrolyte is preferably negative electrode active material:solid electrolyte (mass ratio)=95:5 to 5:95, more preferably 90:10 to 10:90, and further preferably 85:15 to 15:85. If the content of the negative electrode active material in the negative electrode mixture is too small, the electric capacity will be small. In addition, if the negative electrode active material has electronic conductivity and does not contain a conductive additive or contains only a small amount of conductive additive, it is considered that the electronic conductivity (electron conduction path) in the negative electrode will decrease, the rate characteristics will be lowered, the utilization rate of the negative electrode active material will decrease, and the electric capacity will be lowered. On the other hand, if the content of the negative electrode active material in the negative electrode mixture is too high, it is considered that the ionic conductivity (ionic conduction path) in the negative electrode will decrease, the rate characteristics will be lowered, the utilization rate of the negative electrode active material will decrease, and the electric capacity will be lowered.
[0051] The negative electrode mixture may further contain a conductive assistant. When the electronic conductivity of the negative electrode active material is low, it is preferable to add a conductive assistant. The conductive assistant only needs to have electrical conductivity, and the electronic conductivity is preferably 1×10 3 S / cm or more, more preferably 1×10 5 S / cm or more. Specific examples of the conductive assistant are preferably substances containing at least one element selected from the group consisting of carbon materials, nickel, copper, aluminum, indium, silver, cobalt, magnesium, lithium, chromium, gold, ruthenium, platinum, beryllium, iridium, molybdenum, niobium, osmium, rhodium, tungsten, and zinc, and more preferably simple carbon having high conductivity, carbon materials other than simple carbon, or simple metals, mixtures, or compounds containing nickel, copper, silver, cobalt, magnesium, lithium, ruthenium, gold, platinum, niobium, osmium, or rhodium. Specific examples of the carbon material include carbon black such as Ketjen Black, Acetylene Black, Denka Black, Thermal Black, and Channel Black; graphite, carbon fiber, activated carbon, etc., which can be used alone or in combination of two or more. Among them, acetylene black, Denka Black, and Ketjen Black, which have high electronic conductivity, are preferred.
[0052] When the negative electrode composite material contains a conductive assistant, the content of the conductive assistant in the composite material is preferably 1 to 40 mass %, more preferably 2 to 20 mass %. If the content of the conductive assistant is too small, it is considered that the electronic conductivity of the negative electrode may decrease, resulting in a decrease in rate characteristics, or the utilization rate of the negative electrode active material may decrease, resulting in a decrease in electric capacity. On the other hand, if the content of the conductive assistant is too large, the amount of the negative electrode active material and / or the amount of the solid electrolyte may decrease. It is presumed that the electric capacity decreases when the amount of the negative electrode active material decreases. It is also considered that the ionic conductivity of the negative electrode may decrease, resulting in a decrease in rate characteristics, or the utilization rate of the negative electrode active material may decrease, resulting in a decrease in electric capacity.
[0053] In order to tightly bind the negative electrode active material and the solid electrolyte to each other, a binder may further be included. As the binder, fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), fluorine rubber, or thermoplastic resins such as polypropylene and polyethylene, ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, natural butyl rubber (NBR), etc. can be used alone or as a mixture of two or more. In addition, aqueous binders such as cellulose-based and aqueous dispersions of styrene butadiene rubber (SBR) can also be used.
[0054] The negative electrode mixture can be produced by mixing a solid electrolyte, a negative electrode active material, and an optional conductive assistant and / or binder. The mixing method is not particularly limited, but for example, dry mixing using a mortar, ball mill, bead mill, jet mill, planetary ball mill, vibration ball mill, sand mill, cutter mill; and wet mixing using a mortar, ball mill, bead mill, planetary ball mill, vibration ball mill, sand mill, film mix after dispersing the raw material in an organic solvent, and then removing the solvent can be applied. Among these, wet mixing is preferred in order not to destroy the negative electrode active material particles.
[0055] Positive electrode mixture A positive electrode mixture is obtained by blending a positive electrode active material with the solid electrolyte of the present invention. The positive electrode active material is a material capable of inserting and extracting lithium ions, and may be any positive electrode active material known in the battery field, or may be any positive electrode active material to be developed in the future.
[0056] Examples of the positive electrode active material include metal oxides, sulfides, etc. Sulfides include metal sulfides and nonmetal sulfides. The metal oxide is, for example, a transition metal oxide. 2 O 5 , V 6 O 13 , LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4, Li(Ni a Co b Mn c )O 2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-Y Co Y O 2 , LiCo 1-Y Mn Y O 2 , LiNi 1-Y Mn Y O 2 (where 0 ≤ Y < 1), Li(Ni a Co b Mn c )O 4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-Z Ni Z O 4 , LiMn 2-Z Co Z O 4 (where 0 < Z < 2), LiCoPO 4 , LiFePO 4 , CuO, Li(Ni a Co b Al c )O 2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), etc. can be mentioned. As metal sulfides, titanium sulfide (TiS 2 ), molybdenum sulfide (MoS 2 ), iron sulfide (FeS, FeS 2 ), copper sulfide (CuS) and nickel sulfide (Ni 3 S 2 ) etc. can be mentioned. In addition, as metal oxides, bismuth oxide (Bi 2 O 3 ), bismuth lead oxide (Bi 2 Pb 2 O 5 ) etc. can be mentioned. As non-metal sulfides, organic disulfide compounds, carbon sulfide compounds, etc. can be mentioned. In addition to the above, niobium selenide (NbSe 3 ), metal indium, sulfur can also be used as the positive electrode active material.
[0057] The positive electrode mixture may further contain a conductive assistant. The conductive assistant is the same as that in the negative electrode mixture.
[0058] The mixing ratio of the solid electrolyte and the positive electrode active material in the positive electrode mixture, the content of the conductive additive, and the method for producing the positive electrode mixture are the same as those for the negative electrode mixture described above.
[0059] [Lithium-ion battery] A lithium ion battery according to one embodiment of the present invention includes at least one of the sulfide solid electrolyte and electrode mixture of the present invention described above, or is manufactured using at least one of the sulfide solid electrolyte and electrode mixture of the present invention. The structure of the lithium ion battery is not particularly limited, but generally has a structure in which a negative electrode layer, an electrolyte layer, and a positive electrode layer are laminated in this order. Each layer of the lithium ion battery will be described below.
[0060] (1) Negative electrode layer The negative electrode layer is preferably a layer made from the negative electrode mix of the present invention. Alternatively, the negative electrode layer is preferably a layer containing the negative electrode mixture of the present invention. The thickness of the negative electrode layer is preferably from 100 nm to 5 mm, more preferably from 1 μm to 3 mm, and further preferably from 5 μm to 1 mm. The negative electrode layer can be produced by a known method, for example, a coating method or an electrostatic method (electrostatic spray method, electrostatic screen method, etc.).
[0061] (2) Electrolyte layer The electrolyte layer is a layer including or made of a solid electrolyte. The solid electrolyte is not particularly limited, but is preferably the sulfide solid electrolyte of the present invention. The electrolyte layer may be composed of only a solid electrolyte, or may further contain a binder. As the binder, the same binder as that of the negative electrode mixture of the present invention can be used.
[0062] The thickness of the electrolyte layer is preferably 0.001 mm or more and 1 mm or less. The solid electrolyte of the electrolyte layer may be fused. Fusion means that a part of the solid electrolyte particles is dissolved and the dissolved part is integrated with other solid electrolyte particles. The electrolyte layer may be a plate-like body of the solid electrolyte, and the plate-like body may include a case where a part or all of the solid electrolyte particles are dissolved to form a plate-like body. The electrolyte layer can be produced by a known method, for example, a coating method or an electrostatic method (electrostatic spray method, electrostatic screen method, etc.).
[0063] (3) Positive electrode layer The positive electrode layer is a layer containing a positive electrode active material, and is preferably a layer containing the positive electrode mixture of the present invention or a layer produced from the positive electrode mixture of the present invention. The thickness of the positive electrode layer is preferably 0.01 mm or more and 10 mm or less. The positive electrode layer can be produced by a known method, for example, a coating method or an electrostatic method (electrostatic spray method, electrostatic screen method, etc.).
[0064] (4) Current collector The lithium ion battery according to one embodiment of the present invention preferably further includes a current collector. For example, the negative electrode current collector is provided on the side of the negative electrode layer opposite the electrolyte layer side, and the positive electrode current collector is provided on the side of the positive electrode layer opposite the electrolyte layer side. The current collector may be a plate or foil made of copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium, indium, lithium, or an alloy thereof.
[0065] The lithium ion battery according to one embodiment of the present invention can be manufactured by laminating and bonding the above-mentioned components. Examples of bonding methods include a method of laminating the components and applying pressure or pressure to the components by passing them between two rolls (roll to roll). Moreover, the bonding may be performed via an active material having ion conductivity on the bonding surface, or an adhesive material that does not inhibit ion conductivity. The bonding may be performed by heat fusion within a range in which the crystal structure of the solid electrolyte is not changed. The lithium ion battery according to an embodiment of the present invention can also be manufactured by sequentially forming the above-mentioned components. It can be manufactured by a known method, for example, a coating method or an electrostatic method (electrostatic spray method, electrostatic screen method, etc.). EXAMPLES
[0066] The present invention will now be described in more detail with reference to examples. The evaluation method is as follows. (1) Volume-based average particle size (D 50 ) The measurements were made using a laser diffraction / scattering particle size distribution analyzer (HORIBA, LA-950V2 model LA-950W2). A mixture of dehydrated toluene (Wako Pure Chemical Industries, special grade) and tertiary butyl alcohol (Wako Pure Chemical Industries, special grade) in a weight ratio of 93.8:6.2 was used as the dispersion medium. 50 mL of the dispersion medium was injected into the flow cell of the device and circulated, after which the measurement target was added and ultrasonicated, and the particle size distribution was measured. The amount of the measurement target was adjusted so that the red light transmittance (R) corresponding to the particle concentration on the measurement screen specified by the device was within 80 to 90% and the blue light transmittance (B) was within 70 to 90%. In addition, the calculation conditions used were 2.16 as the refractive index of the measurement target and 1.49 as the refractive index of the dispersion medium. In the distribution form setting, the number of repetitions was fixed at 15, and particle size calculation was performed.
[0067] (2) Ionic conductivity measurement The sulfide solid electrolyte produced in each example was filled into a tablet press, and a pressure of 22 MPa was applied to form a compact. Carbon was placed on both sides of the compact as electrodes, and pressure was applied again using the tablet press to produce a compact for measurement (diameter about 10 mm, thickness 0.1 to 0.2 cm). The ionic conductivity of this compact was measured by AC impedance measurement. The conductivity value was measured at 25°C.
[0068] (3) Powder X-ray diffraction (XRD) measurement From the sulfide solid electrolyte produced in each example, a circular pellet with a diameter of 10 mm and a height of 0.1 to 0.3 cm was molded to prepare a sample. This sample was measured using an airtight holder for XRD without exposing it to air. The 2θ position of the diffraction peak was determined by the centroid method using the XRD analysis program JADE. The powder X-ray diffraction measurement was performed using a Rigaku Corporation SmartLab under the following conditions. Tube voltage: 45kV Tube current: 200mA X-ray wavelength: Cu-Kα ray (1.5418Å) Optical system: Parallel beam method Slit configuration: Soller slit 5°, entrance slit 1mm, receiving slit 1mm Detector: Scintillation counter Measurement range: 2θ=10-60deg Step width, scan speed: 0.02 deg, 1 deg / min In the analysis of peak positions to confirm the presence of a crystal structure from the measurement results, the XRD analysis program JADE was used, and the peak positions were obtained by drawing a baseline using a cubic approximation.
[0069] The intensity ratio (Ib / Ip) between the peak intensity Ip of the diffraction peak B and the diffraction intensity Ib of the high-angle side skirt of the diffraction peak B The peak intensity ratio was calculated from the measurement results using Excel spreadsheet software. First, the data was averaged by weighting averaging 7 points, and the averaged value was used to average again by weighting averaging 7 points, and this averaged value was used to average again by weighting averaging 7 points, thereby smoothing the data. Using the smoothed points, a differential curve was created by taking the difference between adjacent smoothed points as the differential value. The maximum measured intensity in the range of 2θ 29.7±0.5 deg was taken as the peak intensity Ip of peak B. The measured intensity at the angle where the differential curve value becomes 0 (the point where it changes from positive to negative) in the high angle region from the maximum intensity was taken as Ib. Ib / Ip was calculated from these values.
[0070] Si relative half-width The minimum diffraction intensity (I back ) was used as the background. The measured peak intensity of diffraction peak B (I BR ) to the background diffraction intensity (I back ) to obtain the peak intensity of diffraction peak B (I B ) was calculated. At diffraction peak B, the peak intensity was I B The two angles (d1, d2) that were half of this angle were obtained, and the difference between d1 and d2 was taken as the half-width A (Δd: measured value). Next, the XRD pattern was measured using Si (Rigaku Corporation) as a sample. si ) and peak intensity (I Si ) was determined in the same manner as the above half-value width A. The background was defined as the minimum diffraction intensity in the range of 2θ from 10 to 60 deg. Half-width A(Δd) and half-width of Si(Δd si ) from the Si relative half-width (Δd / Δd si ) was calculated. In addition, the half-width of Si (Δd si If Δd is 0.3 or more, the measurement is defective. Since there is likely to be a defect in the device itself or the measurement conditions, it is recommended to measure again under appropriate conditions to reduce Δd si is less than 0.3.
[0071] (4)ICP measurement The sulfide solid electrolyte produced in each example was weighed and collected in a vial in an argon atmosphere. An alkaline KOH solution was placed in the vial, and the sample was dissolved while taking care not to collect sulfur, and then appropriately diluted to obtain a measurement solution. This was measured using a Paschen-Runge type ICP-OES device (SPECTRO ARCOS manufactured by SPECTRO) to determine the composition. Calibration curve solutions were prepared using 1000 mg / L standard solutions for ICP measurement for Li, P, and S, and 1000 mg / L standard solutions for ion chromatography for Cl and Br. Two test solutions were prepared for each sample, and five measurements were made for each test solution, and the average value was calculated. The composition was determined by the average of the two test solutions.
[0072] (5)Solid 31 P-NMR measurement Approximately 60 mg of powder sample was loaded into an NMR sample tube and solid-state analysis was performed using the following equipment and conditions. 31 P-NMR spectra were obtained. Equipment: ECZ400R equipment (manufactured by JEOL Ltd.) Observation kernel: 31 P Observation frequency: 161.944MHz Measurement temperature: room temperature Pulse sequence: Single pulse (uses 90° pulse) 90°Pulse width: 3.8μ Waiting time until next pulse application after FID measurement: 300 s Magic angle rotation speed: 12kHz Number of times: 16 Measurement range: 250ppm~-150ppm Chemical shifts: external reference (NH 4 ) 2 HPO 4 (chemical shift 1.33 ppm) was used.
[0073] The obtained solid 31 For the P-NMR spectrum, peaks in the range of 60 to 120 ppm were analyzed using the software "FT-NMR" (software included in "FT-NMR Data Processing by Personal Computer" Revised Edition (2nd Edition) (Sankyo Publishing)) to determine the separated peaks. The above software is 31From the NMR signal (experimental value) in the range of 60 to 120 ppm of the P-NMR spectrum, the nonlinear least squares method is used to calculate the separated peaks, the calculated NMR signal value, and the residual sum of squares R2. When the maximum peak height is set to 1, the residual sum of squares R2 within the analysis range between the experimental value and the calculated value is 0.007 or less, and the number of separated peaks is the smallest. The means and route of peak fitting are not particularly limited, but the following points should be noted. The analysis starts with fitting assuming that the number of separated peaks is basically one. 31 Considering the peak shape of the P-NMR spectrum, the analysis may be started with the number of separated peaks set to 2 or more. For example, if the peak shape of the measured value is asymmetric, or has a shoulder or a tail, the number of separated peaks must be set to 2 or more to achieve R2 of 0.007 or less. Start fitting by inputting appropriate initial values for various parameters. Parameters include peak position (ppm), peak height, and peak half-width (Hz). Starting from the initial values, the software uses the nonlinear least squares method to calculate the separated peaks, the calculated NMR signal values, and the residual sum of squares R2. For peak fitting, a Gaussian function or a Pseudo-Voigt function (a linear sum of a Gaussian function and a Lorentzian function) is used. The function used is based on the Gaussian function, and when accuracy is poor, the Pseudo-Voigt function should be selected. During fitting, the ratio of the Gaussian function and the Lorentzian function of the Pseudo-Voigt function is fixed for calculation, but this fixed value must be determined appropriately. While finely adjusting the above parameters, repeat fitting until R2 is 0.007 or less. If R2 does not become 0.007 or less, increase the number of peaks and perform the same analysis. Finally, when R2 reaches 0.007 or less, peak separation is considered complete. Note that although the standard for R2 is 0.007 or less, a smaller value is better, so fitting can be repeated to improve accuracy.
[0074] Each peak obtained by the analysis has two chemical shifts on either side of the peak that show half the intensity of the maximum value (σ An and σ Bn The half-width Hn (n is an integer of 1 or more) of each separated peak n (n is a peak number and is an integer of 1 or more) was calculated by the following formula. Hn(Hz)=161.944×(σ An -σ Bn ) Area ratio of glass-derived peaks φ カ゛ラス Regarding the separated peaks, those with a half-width of 1000 Hz or more were determined to be peaks derived from glass, and those with a half-width of 450 Hz or less were determined to be peaks derived from crystals.
[0075] Area ratio of each peak φ n (%), the area S of the separated peak n n and its sum S all (=S 1 +S 2 +···+S m : m is an integer of 1 or more) was calculated using the following formula. φ n =100×S n / S all For example, Li is 86 to 87.6 ppm. 3 P.S. 4 Although a small amount of peaks due to β crystals may be observed, in this application, they are considered to be impurities and are excluded from the calculation of the half-width and area ratio. The fact that they are impurities can also be determined from the XRD diffraction pattern. Area ratio of glass-derived peaks φ カ゛ラス The peaks with a half-width of 1000 Hz or more are considered to be glass-derived peaks, and the total area S g and the total area of all peaks S all It was calculated using the following formula: φ カ゛ラス =100×S g / S all Area ratio of each glass-derived peak φ カ゛ラスx The total area S of the peaks derived from each glass gxand the total area S of the glass-derived peaks g It was calculated using the following formula: φ カ゛ラスx =100×S gx / S g
[0076] Regarding the assignment of each peak after peak separation, Table 1 shows an example of a sulfide solid electrolyte containing only chlorine as a halogen, and Table 2 shows an example of a sulfide solid electrolyte containing chlorine and bromine as halogens.
[0077] [Table 1]
[0078] [Table 2]
[0079] (6) Compactibility Compaction was evaluated using a uniaxial compression apparatus. 1 and 2 are schematic diagrams for explaining the compaction evaluation using a uniaxial compression apparatus. The uniaxial compression apparatus mainly comprises a pressure-resistant cylindrical container 1, a pressure rod 2 that applies pressure to the composite placed in the internal space of the cylindrical container 1 to increase the density of the composite to its true density, and a measuring means (micrometer) 3 that measures the height of the composite 5 and a fixture 4 for the measuring means. The cylindrical container 1 used is made of SKD11 and has an outer diameter of 43 mm, an inner diameter of 13 mm, a height of 40 mm, a side thickness of 15 mm, and a bottom diameter of 13 mm and a thickness of 10 mm. SKD11 is a die steel manufactured by Daido Steel Co., Ltd. The pressure rod 2 is smoothly inserted into the cylindrical container 1, has an outer diameter of 13 mm, a length of 50 mm, and is made of SKD11. A pressing means (not shown) for applying pressure is provided on the upper part of the pressure rod 2. Also, a transmission part is provided to transmit the displacement of the pressure rod to a micrometer.
[0080] The void ratio (void ratio upon compression: ε) was measured while compressing the sample at intervals of 108 MPa between 0 and 540 MPa using a uniaxial compression device. First, the micrometer value (l 0 ) (Figure 1). Next, 0.3 g of sample 5 (0.1 g or 0.05 g may be used for samples with high bulk density) is placed inside cylindrical container 1, and the sample is made uniform. The pressure rod 2 is inserted into the container 1, and the sample 5 is compressed by applying pressure of 108 MPa increments between 0 and 540 MPa. The micrometer reading (l 1 ) (Figure 2).
[0081] From the height of the sample when compressed, the void ratio ε (%) can be calculated from the following formula (A). ε = [1-ρ a / ρ p ]×100=[1-{m / (ρ p SL)}]×100 (A) (In the formula, ρ a is the apparent density of the material, ρ p is the true density of the material, m is the weight of the material inserted into the cylindrical container, S is the area of the pressure rod, and L is (l 0 -l 1 )
[0082] The intercept (a) and slope (b) were calculated from Gurnham's equation (logσ=a-bε) for stress σ-void ratio ε. A larger value of b means poorer consolidation. Note that a larger a (when b is constant) indicates that the logσ-ε line shifts toward the larger ε side.
[0083] Manufacturing Example 1 (Lithium sulfide (Li 2 S) Production 200 g of LiOH anhydride (Honjo Chemical Co., Ltd.) dried under inert gas was charged into a 500 mL separable flask equipped with a stirrer. The temperature was raised under a nitrogen stream, and the internal temperature was maintained at 200°C. The nitrogen gas was replaced with hydrogen sulfide gas (Sumitomo Seika Co., Ltd.) at a flow rate of 500 mL / min, and lithium hydroxide anhydride (LiOH) and hydrogen sulfide were reacted. The water generated by the reaction was condensed and collected in a condenser. After 6 hours of reaction, 144 mL of water was collected. The reaction was continued for another 3 hours, but no water was generated. The product powder was collected and the purity and XRD were measured. The purity was 98.5% and the XRD showed Li 2 The peak pattern of S was confirmed.
[0084] Example 1 (1) Preparation of sulfide solid electrolyte (precursor) with argyrodite-type crystal structure Li produced in Production Example 1 2 S and diphosphorus pentasulfide (P 2 S 5 FS SPEC, Thermophos, purity 99.9% or higher) and lithium chloride (LiCl: Sigma-Aldrich, purity 99%) were measured in molar ratio (Li 2 S:P 2 S 5 The starting materials were mixed in a ratio of 19:5:16 (LiCl) (hereinafter, the purity of each starting material was the same in all examples). 200 g of the mixture and 1780 g of zirconia balls with a diameter of 20 mm were placed in a SUS container (volume 6 L). The container was attached to a vibration mill (Chuo Kakoki MD-3) and mechanical energy was applied (mechanical milling process) to obtain a glass (intermediate) that was a whitish yellow powder. The processing conditions for the vibration mill were a nitrogen atmosphere with a dew point of -40°C or less, 40°C, 1500 rpm, and 120 hours.
[0085] About 10 g of the above intermediate powder was packed in a Tammann tube (PT2, manufactured by Tokyo Glass Equipment Co., Ltd.) in a glove box under an Ar atmosphere, the mouth of the Tammann tube was sealed with quartz wool, and the tube was sealed in a SUS airtight container to prevent air from entering. Three identical Tammann tubes were prepared, and the airtight container was then placed in an electric furnace (FUW243PA, manufactured by Advantec Co., Ltd.) and heat-treated. Specifically, the temperature was raised from room temperature to 430°C at a rate of 2.5°C / min (heated to 430°C in about 3 hours), and the temperature was kept at 430°C for 8 hours. After that, the tube was slowly cooled to obtain about 30 g of sulfide solid electrolyte (precursor).
[0086] (2) Processing using a media-less grinder The sulfide solid electrolyte of the present invention was produced by treating 30 g of the precursor in a jet mill (NJ-50, manufactured by Aisin Nanotechnologies Co., Ltd.) in a glove box under a nitrogen atmosphere. The treatment conditions were a treatment speed of 180 g / hour (treatment time: 10 minutes), nitrogen was used as the grinding gas, the input gas pressure was 2.0 MPa, and the grinding gas pressure was 2.0 MPa. The volume-based average particle diameter (D 50 The particle diameter was 3.0 μm. The ionic conductivity (σ) was 3.3 mS / cm. The XRD pattern of the sulfide solid electrolyte is shown in Figure 3. Peaks derived from the argyrodite crystal structure were observed at 2θ = 15.6, 18.1, 25.7, 30.2, 31.6, 45.3, 48.2, and 52.8 deg. From Figure 3, the peak intensity Ip of the diffraction peak at 2θ = 29.7 ± 0.5 deg was 13124. Figure 4 shows the differential curve of the XRD pattern in an enlarged view of the vicinity of 2θ=27 to 33 deg of the XRD pattern shown in Figure 3. From Figure 4, the diffraction intensity Ib of the low-angle side skirt of the diffraction peak at 2θ=29.7±0.5 deg was 1124 (2θ=30.46 deg). The sulfide solid electrolyte was subjected to ICP analysis to measure the molar ratio of each element. As a result, the molar ratio a (Li / P) was 5.4, the molar ratio b (S / P) was 4.4, and the molar ratio c (Cl / P) was 1.6. Figure 5 shows the solid state of sulfide solid electrolyte. 31 The P-NMR spectrum is shown.
[0087] For Example 1 and the following Examples and Comparative Examples, the molar ratios of the elements in the raw materials and the details of the treatment with the pulverizer are shown in Table 3. 31 The area ratios of each peak calculated from the P-NMR measurements are shown in Table 4. The peak intensity Ip of the diffraction peak B of the sulfide solid electrolyte, the diffraction intensity Ib of the high-angle tail of the diffraction peak, the intensity ratio, the Si relative half-width, and the volume-based average particle diameter (D 50 ) are shown in Table 5. The results of the ionic conductivity σ and compactibility evaluation of the sulfide solid electrolyte are shown in Table 6.
[0088] [Table 3]
[0089] [Table 4]
[0090] [Table 5]
[0091] [Table 6]
[0092] Example 2 (1) Preparation of sulfide solid electrolyte (precursor) with argyrodite-type crystal structure Li produced in Production Example 1 2 S and P 2 S 5 , LiCl, and lithium bromide (LiBr, Sigma-Aldrich) in a molar ratio of (Li 2 S:P 2 S 5 The ratio of the starting materials was 1.9:0.5:1.0:0.6, and 30 g of the starting material mixture was obtained. A sulfide solid electrolyte (precursor) was obtained in the same manner as in Example 1, except that the mixture was changed.
[0093] (2) Processing using a media-less grinder Except for setting the input gas pressure to 0.8 MPa and the pulverizing gas pressure to 0.8 MPa, the same treatment as in Example 1 was carried out to produce a sulfide solid electrolyte, which was then evaluated. The results are shown in Tables 3 to 6. From the XRD pattern of the sulfide solid electrolyte, peaks due to the argyrodite-type crystal structure were observed at 2θ=25.2±0.5 deg and 29.7±0.5 deg. The same was true for the examples and comparative examples described later.
[0094] Example 3 A sulfide solid electrolyte was produced and evaluated in the same manner as in Example 2, except that in the treatment with the media-less mill, the input gas pressure was 0.4 MPa and the pulverization gas pressure was 0.4 MPa. The results are shown in Tables 3 to 6.
[0095] Example 4 A sulfide solid electrolyte was produced and evaluated in the same manner as in Example 2, except that a thin film rotary mixer was used as the media-less grinder instead of the jet mill. A thin film rotary mixer (product name "TK Filmix", manufactured by Primix Corporation) was used. 30 g of sulfide solid electrolyte (precursor) was dispersed in 311 mL of toluene as a dispersion medium, and filled into the mixing tank of the device. The rotating blade was attached to the rotating shaft so that the gap between the mixing tank and the rotating blade was 2 mm. The peripheral speed of the rotating blade was set to 30 m / sec, and the treatment was carried out for 180 seconds. The obtained slurry was dried to obtain a sulfide solid electrolyte. The evaluation results are shown in Tables 3 to 6.
[0096] Comparative Example 1 Li produced in Production Example 1 2 S and P 2 S 5 and LiCl in a molar ratio (Li 2 S:P 2 S 5 :LiCl) at a ratio of 1.9:0.5:1.6 to give 30 g of a mixture of starting materials. The raw material mixture and 30 g of zirconia balls with a diameter of 10 mm were placed in a zirconia pot (45 mL) of a planetary ball mill (manufactured by Fritsch: model number P-7) and completely sealed. The pot was filled with an argon atmosphere. The planetary ball mill was rotated at 370 rpm and processed (mechanical milling) for 15 hours to obtain a glassy powder (intermediate). The intermediate was heat-treated in the same manner as in Example 1 to produce a precursor. The obtained precursor was dispersed in 750 mL of a solvent (dehydrated toluene, manufactured by Wako Pure Chemical Industries, Ltd.) in a glove box under a nitrogen atmosphere to obtain a slurry of about 5.8 wt%. The slurry was ground using a bead mill (LMZ015, manufactured by Ashizawa Finetech Co., Ltd.) while keeping the slurry in a nitrogen atmosphere. Specifically, 456 g of zirconia beads with a diameter of 0.5 mm were used as the grinding medium, and the bead mill was operated under conditions of a peripheral speed of 12 m / sec and a flow rate of 500 mL / min, and the slurry was put into the device and passed through it once. The treated slurry was placed in a Schlenk flask substituted with nitrogen, and then dried under reduced pressure to obtain a sulfide solid electrolyte. The evaluation results of the sulfide solid electrolyte are shown in Tables 3 to 6. The XRD pattern of the sulfide solid electrolyte is shown in FIG.
[0097] Comparative Example 2 Li 2 S, P 2 S 5 and the molar ratio of LiCl (Li 2 S:P 2 S 5 The raw materials were mixed so that the ratio of Li:LiCl was 2.5:0.5:1.0. 2 S0.642g, P 2 S 5 0.621 g of ZnO and 0.237 g of LiCl were mixed to prepare a raw material mixture. The raw material mixture and 30 g of zirconia balls with a diameter of 10 mm were placed in a zirconia pot (45 mL) of a planetary ball mill (Fritsch: Model No. P-7) and completely sealed. The pot was filled with an argon atmosphere. The planetary ball mill was rotated at 370 rpm and processed (mechanical milling) for 15 hours to obtain a glassy powder (intermediate).
[0098] Approximately 1 g of the intermediate powder was packed in a Tammann tube (PT2, manufactured by Tokyo Glass Equipment Co., Ltd.) in a glove box under an Ar atmosphere, the mouth of the Tammann tube was sealed with quartz wool, and the tube was sealed in a SUS airtight container to prevent air from entering. The airtight container was then placed in an electric furnace (FUW243PA, manufactured by Advantec Co., Ltd.) and heat-treated. Specifically, the temperature was raised from room temperature to 430°C at a rate of 2.5°C / min (heated to 430°C in about 3 hours), and the temperature was kept at 430°C for 8 hours. The mixture was then slowly cooled to obtain a sulfide solid electrolyte. The obtained sulfide solid electrolyte was evaluated, and the evaluation results are shown in Tables 3 to 6.
[0099] Comparative Example 3 0.5 g of glass (intermediate) obtained in the same manner as in Example 1(1), 1.5 g of sulfide solid electrolyte (precursor) obtained in the same manner as in Example 1(1), and 30 g of zirconia balls with a diameter of 2 mm were placed in a zirconia pot (45 mL) of a planetary ball mill (manufactured by Fritsch: model number P-7) and completely sealed. An argon atmosphere was created inside the pot. The mixture was treated in the planetary ball mill at a rotation speed of 100 rpm for 0.5 hours to obtain a sulfide solid electrolyte. The evaluation results are shown in Tables 3 to 6.
[0100] [Lithium-ion battery] A lithium ion battery was manufactured using the sulfide solid electrolyte obtained in each example, and the capacity retention rate was evaluated.
[0101] (A) Lithium-ion battery manufacturing 50 mg of the sulfide solid electrolyte obtained in each example was placed in a stainless steel mold with a diameter of 10 mm, flattened to ensure that the thickness of the electrolyte layer was uniform, and then pressure-molded by applying a pressure of 185 MPa from the top surface of the electrolyte layer using a hydraulic press (P-6, manufactured by RIKEN). Li as the positive electrode active material 4 Ti 5 O 12 Coat LiNi 0.8 Co 0.15 Al 0.05 O 2The sulfide solid electrolytes obtained in each example were mixed in a weight ratio of 70:30 to form the positive electrode material, and 15 mg of the positive electrode material was poured onto the top surface of the electrolyte layer and flattened to ensure that the thickness of the positive electrode layer was uniform. After that, a pressure of 407 MPa was applied to the top surface of the positive electrode layer using a hydraulic press (P-6, manufactured by RIKEN) to form a pressure mold. The negative electrode material was prepared by mixing the graphite powder, which is the negative electrode active material, and the sulfide solid electrolyte obtained in each example in a weight ratio of 60:40. 12 mg of the negative electrode material was placed on the side of the electrolyte layer opposite the positive electrode layer and flattened to make the layer thickness of the negative electrode layer uniform. After that, a hydraulic press (P-6, manufactured by RIKEN) was used to apply a pressure of 555 MPa from the top of the negative electrode layer to pressure mold it, producing a lithium-ion battery with a three-layer structure of a positive electrode, a solid electrolyte layer, and a negative electrode.
[0102] (B) Cycle characteristic test The lithium-ion battery manufactured in (A) above was left in a thermostatic chamber set at 25°C for 12 hours and then evaluated. In the first cycle, it was charged to 4.2V at 0.1C (0.189mA) and discharged to 3.1V at 0.1C (0.189mA). In the second to tenth cycles, it was charged to 4.2V at 0.5C (0.945mA) and discharged to 3.1V at 0.5C (0.945mA). In the eleventh cycle, it was charged to 4.2V at 0.1C (0.189mA) and discharged to 3.1V at 0.1C (0.189mA). From the 1st to 16th cycles, the battery was charged to 4.2V at 0.2C (0.378mA), and discharged to 3.1V at 0.2C (0.378mA), 0.5C (0.945mA), 1C (1.89mA), 2C (3.78mA), and 5C (9.45mA) for each cycle. From the 17th to 19th cycles, the battery was charged to 4.2V at 0.5C (0.945mA), and discharged to 3.1V at 0.5C (0.945mA). From the 20th cycle, the battery was charged to 4.2V at 0.1C (0.189mA), and discharged to 3.1V at 0.1C (0.189mA). After that, for 19 cycles (21st to 39th cycles), the battery was charged to 4.2V at 0.5C (0.945mA) and discharged to 3.1V at 0.5C (0.945mA). For the next cycle (40th cycle), the battery was charged to 4.2V at 0.1C (0.189mA) and discharged to 3.1V at 0.1C (0.189mA). This 20 cycles constituted one set, and this was repeated four times to make a total of 100 cycles. The capacity retention rate was the ratio of the discharge capacity at the 100th cycle to the maximum discharge capacity during the cycle. The capacity retention rate is shown in Table 7.
[0103] [Table 7]
[0104] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all documents cited in this specification and of the application from which this application claims priority under the Paris Convention are incorporated by reference in their entirety.
Claims
1. A method for producing a sulfide solid electrolyte precursor having an argyrodite-type crystal structure containing lithium, phosphorus, and sulfur by heat treatment; and treating the precursor with a media-less grinder. A method for producing a sulfide solid electrolyte, which contains an argyrodite-type crystal structure and glass, and has a diffraction peak A at 2θ=25.2±0.5 deg and a diffraction peak B at 29.7±0.5 deg in powder X-ray diffraction using CuKα radiation.
2. The method for producing a sulfide solid electrolyte according to claim 1 , wherein the media-less grinder is an airflow grinder or a thin film rotary mixer.
3. The method for producing a sulfide solid electrolyte according to claim 1 , wherein the media-less grinding machine is a jet mill.
4. The method for producing a sulfide solid electrolyte according to claim 1, wherein the heat treatment temperature is 350 to 480° C.
5. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 4, wherein no heat treatment is performed after the treatment in the media-less grinder.
Citation Information
Patent Citations
Solid electrolyte microparticle and its manufacturing method
JP2008004459A
Solid electrolyte and all-solid secondary battery using it
JP2008103203A
Solid electrolyte and its manufacturing method
JP2009211950A
Lithium silver sulfide germanium ore
JP2010540396A
Sulfide-based solid electrolyte for lithium ion batteries
JP2016024874A